Coastal shipping policy in New Zealand: Economy wide implications - Cavana, R.Y (School of Management Working Papers, 1993)
Government recently introduced the Transport Law Reform Bill, which if passed by Parliament, will allow foreign vessels to uplift and discharge cargoes and passengers along the coast of New Zealand. Coastal shipping is part of the domestic transport industry along with other transport modes including road, rail and air. The domestic transport industry currently operates on a "level playing field" in a highly competitive and efficient industry, which has benefitted from deregulation and considerable restructuring over the last decade. This paper presents a brief review of the coastal shipping industry in New Zealand and an overview of international cabotage laws. An alternative open coast shipping policy proposed by the New Zealand Shipping Federation, which is based on reciprocity and "level playing fields " principles, is presented. The scope of cost benefit analysis is outlined and the economy wide implications of the potential costs and benefits of the Government's open coast shipping policy are summarised. The potential costs to New Zealand include the effects on employment, equity, Government finances, regional development, service levels, the environment, primary industry and national defence strategy. The potential benefits primarily relate to the economic effects of possible lower freight rates, particularly for traffic from the North Island to the South Island, the route taken by most cross traders. Government officials have prepared a Cabinet paper, which was subsequently agreed to by Government, recommending opening up the coasts to foreign vessels without undertaking an empirical costs benefit analysis. The Government officials' background papers related to this Cabinet paper have been obtained through the Official Information Act and these have been analysed. Based on this work it appears that the case for an open coast policy is far from convincing, and in actual fact there appears to be considerable evidence to suggest that the potential costs to New Zealand far outweigh the potential benefits. The conclusion of this paper suggests that Clause 240 (and other clauses) of the Transport Law Reform Bill relating to an open coast policy should be withdrawn and a full empirical cost benefit analysis should be undertaken to determine the best coastal shipping policy for New Zealand.